The impact of social capital on health behaviors: evidence from urban China - Niu, Long; Lu, Chuntian; Quan, Xiaojuan (Frontiers in Public Health, 2025)
BackgroundSocial capital plays a crucial role in sustaining individual health behaviors. While numerous studies have confirmed the positive impact of social capital on individual health outcomes, limited research has explored its influence on specific health behaviors. Based on data from Job Search and Social Networks 2014 (JSNET 2014) in eight China cities, this study assesses social capital through the occupational heterogeneity of the Bainian Network and the breadth of participation in the Dining Network, aiming to analyze the influence of social capital on health behaviors.MethodsFirst, given that the dependent variable is ordinal, this study employs an ordinal logistic regression model (ordered logistic model) to estimate the cumulative odds of social capital affecting health behaviors. Second, it examines the relationship between social capital and positive health behaviors, including exercise frequency and routine health checkups. Finally, it explores the association between social capital and negative health behaviors, specifically the frequency of alcohol consumption and smoking. All data analyses were conducted using Stata 17.0.Results(1) Social capital significantly influences both positive and negative health behaviors. (2) There is a positive correlation between social capital and health-promoting behaviors, such as physical activity and routine medical checkups. (3) The relationship between social capital and negative health behaviors-such as increased alcohol consumption and smoking frequency-underscores the dual nature of social networks, which can either foster positive behaviors or reinforce unhealthy habits.ConclusionThe findings suggest that social capital has a dual impact: it promotes positive health behaviors such as physical exercise and regular health checkups, while also reinforcing negative health behaviors like drinking and smoking. Nonetheless, these findings are limited to urban population, and future research should extend to rural population to provide a more comprehensive understanding.